Structure-Based Virtual Screening and Molecular Dynamics of Quercetin and Its Natural Derivatives as Potent Oxidative Stress Modulators in ROS-induced Cancer - Abd. Kakhar Umar; James H. Zothantluanga (Indonesian Journal of Pharmaceutics, 2021)
Quercetin derivatives are known to have significant anticancer activity. The activity is strongly influenced by the type and position of the substituent group. By studying the structural pattern of quercetin and its impact on their binding affinity, the development of quercetin-based drugs can be optimized. The study aimed to determine the impact of 3D structure, type, and position of quercetin moiety on its activity against ROS-modulating enzymes that play a role in the induction and growth of ROS-induced cancer. The 23 natural quercetin derivatives were docked to 7 ROS-modulating enzymes using Autodock Vina to determine their binding affinity and interaction. The interaction stability was further studied through molecular dynamics simulation using the CABS Flex 2.0 server. Determination of crucial amino acid targets of the quercetin group was determined using DockFlin. Finally, the toxicity of each test ligand was determined using the pkCSM server. The highest binding affinity for SOD and NOX was produced by quercetin 3'-glucoside with the binding energy of -10.2 and -12.8 kcal/mol. Quercetin 3,4'-diglucoside had the highest binding affinity for CAT and GR at -11.5 and -10.5 kcal/mol, respectively. Routine produced the highest binding affinity at LOX (-10.9). Quercetin 3-O-xyloside and quercetin 3-O-rhamnoside-7-O-glucoside had the highest binding affinity in XO with a value of -10.4 kcal/mol. The glucose and prenyl groups are beneficial for quercetin in interacting with all ROS-modulating enzymes except XO. In contrast, the methoxy group negatively affects all interactions of quercetin with receptors. The perfect fit between the binding pocket and the 3D structure of the ligand greatly benefits the ligand in accessing more amino acids in the binding pocket. Their interaction stability and toxicity show that quercetin 3'-glucoside, quercetin 3,4'-diglucoside, and rutin are potent oxidative stress modulators in treating ROS-induced cancer.